Resistance of European plum to fungal diseases in the foothill zone of Adygea - V. V. Sherstobitov; M. A. Kolesova (Труды по прикладной ботанике, генетике и селекции)
Background. European plum (Prunus domestica L.) is a widespread stone fruit crop in Krasnodar Territory and Adygea. Development of fungal diseases, including brown rot, shot hole, red leaf spot, and rust, leads to a significant decrease in the harvest and marketable quality of P. domestica fruits. Therefore, breeding for resistance to these diseases is very important for planting highly productive European plum orchards. The objective of this study was to identify P. domestica cultivars resistant to four fungal diseases under the conditions of the foothill zone of Adygea.   Materials and methods. The research material included 25 P. domestica cultivars from the collection orchard of Maikop Experiment Station of VIR. Resistance to fungal diseases was assessed in 2011–2022 using a conventional scale.   Results and conclusions. Weather and climate conditions during the flowering, fruit growth and ripening periods of European plum affected the degree of damage inflicted by fungal diseases. Many years of testing resulted in identifying P. domestica cultivars with different scores of resistance to brown rot, shot hole, and rust. Ten P. domestica cultivars were characterized by group resistance to the abovementioned diseases: ‘Anna Shpet’ (k-3325), ‘Vengerka Rannyaya’ (k-3459), ‘Vengerka Italyanskaya’ (k-3444), ‘Musa Dzhaliev’ (k-26994), ‘Vengerka Vkusnaya’ (k-43323), ‘Persikovaya Michurina’ (k-30706), ‘Chernosliv Adygeyskiy’ (k-23743), ‘Chernosliv Shuntukskiy’ (k-23707), ‘Yekaterina’ (yellow) (k-3520), and ‘Vasсova’ (k-27639). They can be recommended to plum breeders for the development of P. domestica cultivars with group resistance to fungal diseases in the foothill zone of Adygea.